AUTONOMY LIMITATIONS IN PUBLIC HEALTH LAW: COMPULSORY CHILDHOOD VACCINATION - Tucak, Ivana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
It needs to be stressed that the opponents of compulsory vaccination programmes for children, which are nowadays preferred by many states, are not unanimous in their arguments against such policies. Since its very beginnings, this preventive medical measure has, among other things, induced ’scientific objections’ to its effectiveness and safety, conscientious objections (of religious and philosophical origin) and objections to restrictions imposed by the state with respect to human freedoms and bodily integrity. The purpose of this paper is to provide a critical overview of ethical and legal issues related to compulsory vaccination. For some time now scientific circles have been preoccupied with the issue if the benefits of compulsory vaccination can prevail over all the problems caused thereby. The paper is also aimed at setting a limit on the state interference with personal autonomy and parental freedoms. This issue have broader political and social repercussions which are reflected in legislative and judicial discussions. In addition, special light is shed on the reasons behind the Ruling of the Constitutional Court of the Republic of Croatia of 30 January 2014 dismissing the application for initiation of the procedure for assessment of compliance of particular provisions of the Act on the Protection of the Population against Communicable Diseases with the Constitution.